Activities of Eravacycline, Tedizolid, Norvancomycin, Nemonoxacin, Ceftaroline, and Comparators against 1,871 Staphylococcus and 1,068 Enterococcus Species Isolates from China: Updated Report of the CHINET Study 2019 - Li Ding; Yang Yang; Changhe Zheng; Gang Sun; Renru Han; Yan Guo; Dandan Yin; Shi Wu; Demei Zhu; Fupin Hu (Microbiology Spectrum, 2022)
ABSTRACT To evaluate the in vitro activities of eravacycline, tedizolid, nemonoxacin, norvancomycin, and ceftaroline against Staphylococcus and Enterococcus species isolates were collected as part of the China Antimicrobial Surveillance Network (CHINET) in 2019 to provide susceptibility data for Staphylococcus spp. and Enterococcus spp. for their future development and application in clinical practice. Antimicrobial susceptibility testing was performed using the CLSI broth microdilution reference method. Eravacycline was highly active against Staphylococcus and Enterococcus species isolates, proved by the MIC50/90: 0.06/0.125, 0.06/0.25, 0.06/0.25, 0.06/0.25, 0.125/0.5, 0.125/0.25, and 0.03/0.06 mg/L for Staphylococcus aureus, methicillin-resistant S. aureus (MRSA), S. epidermidis, S. hominis, S. haemolyticus, Enterococcus faecalis, and E. faecium, respectively. S. aureus isolates tested were fully susceptible to tedizolid. Still, nonsusceptible isolates were found for E. faecalis (72/567 [12.7%]) and E. faecium (12/501 [2.4%]). Norvancomycin at 2 mg/L could inhibit 100% of Staphylococcus spp., while 1 mg/L of ceftaroline could inhibit 78.9% of MRSA and 99.9% of methicillin-susceptible S. aureus (MSSA) isolates. Additionally, nemonoxacin was also active against Staphylococcus and Enterococcus species isolates tested (shown by the following MIC90s and ranges, in milligrams per liter: 2 and ≤0.015 to 8 for MRSA, 0.25 and ≤0.015 to 4 for MSSA, 0.5 and ≤0.015 to 8 for S. epidermidis, and 4 and ≤0.015 to >32 for E. faecalis). In conclusion, both eravacycline and tedizolid were highly active against clinical isolates of Staphylococcus spp. and Enterococcus spp. recently collected across China. Nemonoxacin showed potent activity against Staphylococcus spp. and E. faecalis but limited activity against E. faecium. Norvancomycin and ceftaroline displayed highly potent activity against Staphylococcus spp. IMPORTANCE Antimicrobial resistance has become a severe threat to global public health. According to statistics, nearly 700,000 people die from bacterial infections worldwide (J. O’Neill, Antimicrobial Resistance: Tackling a Crisis for the Health and Wealth of Nations, 2014; C. Y. Chin, K. A. Tipton, M. Farokhyfar, E. M. Burd, et al., Nat Microbiol 3:563–569, 2018, https://doi.org/10.1038/s41564-018-0151-5). The number of bacterial infections is expected to climb to 10 million by 2050, showing that bacterial resistance has become a significant problem that cannot be ignored. It is crucial to develop new antimicrobial agents to combat antimicrobial-resistant bacteria. In this study, we evaluated the in vitro activities of eravacycline, tedizolid, nemonoxacin, norvancomycin, and ceftaroline against Staphylococcus spp. and Enterococcus species isolates which were collected as part of CHINET in 2019. We believe that this study can provide susceptibility data for Staphylococcus spp. and Enterococcus spp. for their future development and application in clinical practice.